Bioprocess Development in Single‐Use Systems for Heterotrophic Marine Microalgae. Issue 1 (13th November 2012) - Hillig, Friederike; Annemüller, Steffi; Chmielewska, Magdalena; Pilarek, Maciej; Junne, Stefan; Neubauer, Peter; Eibl, Regine; Eibl, Dieter
Abstract The utilization of single‐use systems is more and more common in upstream cultivation in biotechnological processes. The advantages of single‐use bioreactors for the cultivation of the heterotrophic microalgae Crypthecodinium cohnii serves as an example for the feasibility of polymer based orbital shaken systems for shear‐sensitive microorganisms with a high oxygen demand. Experiments in the shake flask scale indicate the advantage of tubes like the TubeSpin Bioreactor 600 in comparison to standard Erlenmeyer flasks. In the screening stage, performed in orbitally shaken deepwell plates, the growth performance is significantly improved by the application of perflourodecalin for the modulation of the gas transfer. The use of orbitally shaken systems from the deepwell plate format over the TubeSpin towards orbitally shaken bioreactors provides a reliable strategy for the consistent bioprocess development and scale up of shear‐sensitive aerobic microorganisms. The consistent scalability of the process up to 200 L is envisaged.